SWOT Analysis of Secondary School Education of Bangladesh: Intern Teachers’ Insights from the Government High Schools in Chattogram - Mannan, Abdul; Hossain, Md. Kabir (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
The study explored intern teachers' perceptions of the existing scenario of government secondary schools. A qualitative SWOT analysis was conducted in five key areas of the school environment. The sample consisted of 30 intern teachers selected from rural and urban areas of Chattogram district, Bangladesh. The data were collected through a semi-structured interview schedule with participants who recently completed a three-month internship and were analyzed following the themes. The findings indicate that some strengths of government secondary schools, as opined by the intern teachers, include supportive SMCs, dedicated leadership, active alumni participation, and well-equipped facilities. On the other hand, regarding the weaknesses of government schools, the study uncovered several aspects: a shortage of teachers, inadequate administrative staff, low community participation, outdated infrastructure, a lack of modern technology, and overcrowded classrooms. Additionally, the study identified opportunities in both the management system and the teaching-learning environment. The threats to the schools included the lottery-based admission process, political interference, and funding shortage. It is expected that the findings of the study will provide implications for policymakers, educators, educational administrators, and secondary school teachers in addressing the current situation to ensure quality education.